2005
DOI: 10.1007/s10461-005-1679-y
|View full text |Cite
|
Sign up to set email alerts
|

Drug Sharing Among Heroin Networks: Implications for HIV and Hepatitis B and C Prevention

Abstract: Qualitative and quantitative findings from the baseline survey of a longitudinal, socially-focused blood-borne disease intervention study among 611 heroin IDU in Denver indicate that high risk injection practices-the sharing of contaminated drug solution in particular-often occur as a consequence of how heroin is obtained, the quantity obtained and the setting where it is injected. Contamination occurs if a contaminated syringe is used to liquefy and apportion the shared drug. In our cohort of 304 heroin injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 55 publications
8
101
1
Order By: Relevance
“…Injecting in public places has been associated with risky injection behaviors and HIV seroconversion in several studies [15,[35][36][37]]-a consequence of hurrying injection to minimize risk of police detection and arrest. This is a particularly common practice among homeless IDUs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Injecting in public places has been associated with risky injection behaviors and HIV seroconversion in several studies [15,[35][36][37]]-a consequence of hurrying injection to minimize risk of police detection and arrest. This is a particularly common practice among homeless IDUs.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 92% were male and 99% considered themselves Hispanic or Latino. Median age was 34 years [interquartile range (IQR): [28][29][30][31][32][33][34][35][36][37][38][39][40] and median time since first injection was 12.5 years (IQR: [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Study Populationmentioning
confidence: 99%
“…Prevalence of Injecting Behaviors Varies The prevalence of syringe sharing varies by site from approximately 22 to 62% [41][42][43] and may be decreasing in some sites. 44 Sharing of drug solution and equipment may be more common than sharing of syringes.…”
Section: 40mentioning
confidence: 99%
“…Injection of drug residues has been previously described among heroin users in the western United States, where black tar was the most prevalent form of heroin (Bourgois, 1998;Koester et al, 2005;Bourgois and Schonberg, 2009). Ethnographers observed that similar to some PO formulations, black tar heroin was not easily dissolvable and left significant amounts of residues in filters used for injection.…”
Section: Introductionmentioning
confidence: 98%
“…To date, only four studies have looked at the prevalence of drug residue injection, focusing on injecting someone else's drug residue (Koester et al, 2005;Evans et al, 2009;Le Marchand et al, 2013). To our knowledge, PO residue injection has never been measured or discussed explicitly in epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%